2015
DOI: 10.1212/wnl.0000000000002149
|View full text |Cite
|
Sign up to set email alerts
|

Risk of rupture of unruptured cerebral aneurysms in elderly patients

Abstract: Objectives:The aim of this study was to identify risk factors for rupture of unruptured cerebral aneurysms (UCAs) in elderly Japanese patients aged 70 years or older.Methods:The participants included all patients 70 years of age or older in 3 prospective studies in Japan (the Unruptured Cerebral Aneurysm Study of Japan [UCAS Japan], UCAS II, and the prospective study at the Jikei University School of Medicine). A total of 1,896 patients aged 70 years or older with 2,227 UCAs were investigated. The median and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…Kim et al believed that a sidewall aneurysm found with multiple aneurysms or an AcomA aneurysm found from a patient with hypertension may be prone to rupture at smaller sizes. In a prospective study in Japan (29), patient age and PcomA were reported to be significant risk factors for rupture in the elderly patients. Similarly, our results show that small ruptured cerebral aneurysms at the location of the PcomA are more common and the proportion of multiple aneurysms is higher in the elderly patients compared with those in the nonelderly patients.…”
Section: Discussionmentioning
confidence: 96%
“…Kim et al believed that a sidewall aneurysm found with multiple aneurysms or an AcomA aneurysm found from a patient with hypertension may be prone to rupture at smaller sizes. In a prospective study in Japan (29), patient age and PcomA were reported to be significant risk factors for rupture in the elderly patients. Similarly, our results show that small ruptured cerebral aneurysms at the location of the PcomA are more common and the proportion of multiple aneurysms is higher in the elderly patients compared with those in the nonelderly patients.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, only 89.3% of the elderly patients with UA were in good preoperative condition with mRS 0–2, and the remaining patients with poor preoperative condition should not be treated. Taking into consideration that the rupture risk of unruptured aneurysm in the elderly patients is about 3.6%, 24) indication of NET for UA in the elderly patients should be decided strictly.…”
Section: Discussionmentioning
confidence: 99%
“…20) Higher age is a significant risk factor for UCA rupture in elderly patients. 49) The Japanese population includes a very high proportion of elderly individuals and Japan has the highest life expectancy at birth worldwide, according to health data from the OECD. 50) Therefore, many elderly patients aged over 65 years old receive treatment for UCAs in Japan.…”
Section: Treatment For Ucamentioning
confidence: 99%